Fit in celebrity–charity alliances: when perceived celanthropy benefits nonprofit organisations. Issue 3 (26th June 2014) - Ilicic, Jasmina; Baxter, Stacey
<x xml:space="preserve">Abstract</x> This study investigates the effect of celebrity–charity co‐branding fit on perceived celebrity philanthropy (celanthropy), attitude towards the celebrity and charity, as well as donation intention. We manipulate celebrity–charity functional fit through a 2 (celebrity: comedian vs athlete) × 2 (charity: comedy related vs sports related) factorial design whilst controlling for celebrity credibility (attractiveness, trustworthiness and expertise). Results show that a functional fit between the celebrity and charitable organisation encourages positive altruistic attributions in terms of perceptions of celebrity social responsibility, and egoistic attributions, with regards to celebrity and charity attitudes, and donation intention. Finally, results demonstrate that celebrity–charity fit (athlete (comedian) with sports related (comedy related) charity) can promote positive attitudes towards a celebrity and charity brand, as well as donation intention, with these relationships mediated by perceptions of celebrity social responsibility or philanthropy. Findings from this research are able to aid nonprofit organisations and celebrity brand managers in the creation of effective and persuasive co‐branding alliances. Copyright © 2014 John Wiley & Sons, Ltd.